The Contribution of Sex Difference on Different Liver Histopathology Between Male and Female Mice After Oral Administration of Caffeine - Muhammad Sholikhuddin Nafi’; Tri Hartini Yuliawati; Prijati Sri Irawati; Nurina Hasanatuludhhiyah (Universitas Airlangga, 2021)
Background: There are several studies reporting the effect of caffeine on liver histopathology, but it remains controversy. The laboratory animal used in those studies were predominantly male, whereas there is contribution of sex difference on different liver reaction to xenobiotic between male and female subject. Objective: It is necessary to conduct a study to explore the differences between the liver histopathology of male and female mice after oral administration of caffeine. Methods: This study used 36 mice (Mus musculus) that were divided into 4 groups: male & female untreated groups and male & female treated groups which were orally administered with caffeine 0.4 mg / 20 gramBW daily for 30 days. At the end of treatment, mice were euthanized and dissected. Histopathological examination was done to determine the percentage of liver cell death of each group. Results: The percentage of liver cell deathin female treated group was higher than male treated group (p = 0.0001). But there was no significant difference of liver cells death between male control and treated group and between female control and treated group. Conclusion: There was significant difference in liver histopathology between male and female mice after oral administration of caffeine.